Ectasia detection by anterior segment optical coherence tomography in scheimpflug tomographically normal keratoconus fellow eyes - Naujokaitis, Tadas; Augustin, Victor A.; Son, Hyeck Soo; Köppe, Maximilian; Kovalchuk, Bogdana; Auffarth, Gerd U.; Khoramnia, Ramin (Cornea, 2024)
Purpose: The purpose of this study was to determine whether the Scheimpflug tomographically normal fellow eyes of keratoconus patients are also classified as normal using an ectasia screening algorithm based on anterior segment optical coherence tomography (AS-OCT). Methods: This monocentric cross-sectional study included 22 very asymmetric ectasia patients with tomographically significant keratoconus in 1 eye and normal Scheimpflug tomography in the fellow eye. Twenty-two eyes of 22 healthy subjects served as a control group. We performed corneal tomography using Pentacam AXL (Oculus, Wetzlar, Germany) and used Belin/Ambrósio Enhanced Ectasia total deviation index as well as Belin ABCD keratoconus classification to identify Scheimpflug tomographically normal eyes. We also performed AS-OCT using Anterion (Heidelberg Engineering, Heidelberg, Germany) and analyzed for the presence of ectasia using the Screening Corneal Objective Risk of Ectasia (SCORE) algorithm, with positive values indicating ectasia suspect tomography. - Results: The SCORE value was positive in 9.1% (n = 2) of the healthy eyes, in 45.5% (n = 10) of the Scheimpflug tomographically normal eyes of keratoconus patients and in all eyes (n = 22) with tomographically significant keratoconus. The Scheimpflug tomographically normal eyes of keratoconus patients had higher SCORE values compared with healthy controls (P < 0.001). The median (interquartile range) SCORE value was −1.7 (1.3) in healthy controls, −0.5 (2.2) in Scheimpflug tomographically normal eyes of keratoconus patients, and 11.1 (11.0) in tomographically significant keratoconus eyes. - Conclusions: The Scheimpflug tomographically normal fellow eyes of keratoconus patients had higher AS-OCT-based SCORE values than healthy controls, with positive SCORE values found in 46% of the eyes, indicating early tomographic ectatic changes.
Gesehen am 26.11.2024